A neutral magnetic bioactive glass and its preparation method and application
The nanoparticle silicon-based porous materials loaded with calcium sulfate, magnesium oxide and iron tetraoxide are subjected to low-temperature calcination, which solves the high temperature and high cost problems of preparing neutral magnetic bioactive glass in the prior art, and realizes the neutral properties of the material and excellent magnetothermal effects, which are suitable for bone tumor treatment.
Patent Information
- Application Number
- CN202310389722.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-04-12
AI Technical Summary
The prior art is difficult to prepare neutral magnetic bioactive glass at low cost and low temperature calcination, and traditional methods will lead to the conversion of iron tetroxide to α-ferrous oxide, reducing magnetothermal effects, and generating alkaline calcium oxide, affecting biocompatibility.
Nanoparticle silicon-based porous materials supported by calcium sulfate, magnesium oxide and iron tetraoxide are used for low-temperature calcination, and the calcination temperature is not higher than 450℃ to avoid the conversion of iron tetraoxide to α-iron oxide and maintain the neutral properties of the material.
The preparation of neutral magnetic bioactive glass is realized. The material has excellent biological activity, biocompatibility and osteogenic ability, and has excellent magnetothermal effects, which is suitable for the treatment of bone tumors.
Smart Images

Figure CN116621458B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a neutral magnetic bioactive glass and a preparation method and application thereof. Background Art
[0002] Bone tumors have always been a difficult problem in the field of orthopedics. After removing the lesions and implanting bone repair materials, they are still prone to recurrence, causing great pain to patients. However, tumor cells have poor heat resistance. When the temperature reaches above 40°C, tumor cells can be effectively killed, which brings new directions to the treatment of bone tumors. Due to the magnetocaloric effect, when bone implant materials are magnetic, a large amount of heat will be generated in an alternating magnetic field. After implantation in the body, tumor cells can be effectively killed through long-term heat treatment, so magnetic bone implant materials are an effective means of treating bone tumors.
[0003] Bioactive glass is a type of bone implant material with good bioactivity, good performance and biocompatibility. Combined with magnetic materials such as ferroferric oxide or γ-iron oxide, the material can have both magnetocaloric ability and osteogenic ability, thereby achieving the purpose of treating bone tumors. Traditional bioactive glass is made by calcining oxides such as calcium oxide, silicon dioxide, phosphorus pentoxide and sodium oxide at a high temperature of more than 1300°C, but it has high requirements for equipment, the production process is relatively dangerous, and it will cause ferroferric oxide or γ-iron oxide to be converted into α-iron oxide and lose its magnetism. The preparation method of the second-generation bioglass is the gel method, which uses tetraethyl orthosilicate, triethyl phosphate, calcium nitrate, etc. to hydrolyze under acid or base catalysis, and then age, dry and calcine. This method can greatly reduce the calcination temperature and obtain bioactive glass with a high specific surface area and biological activity. However, like the first-generation bioactive glass, it is an alkaline material. After being implanted into the human body, it often causes greater stimulation to the tissue, causing tissue redness and swelling, and also causes part of ferroferric oxide or γ-iron oxide to be converted into α-iron oxide. Patent CN202110861253.8 introduces a magnetic bioactive glass, which has good biological activity and magnetocaloric capacity. However, due to the addition of calcium nitrate in the reaction, a calcination temperature of more than 650°C is required, which causes part of the ferroferric oxide to be converted into α-ferric oxide, reducing its magnetocaloric effect. At the same time, the generated calcium oxide leads to higher alkalinity.
[0004] Therefore, how to develop a method with low calcination temperature, simple process and low cost to prepare a magnetic bioactive glass with high neutral bioactivity has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a neutral magnetic bioactive glass and a preparation method and application thereof, which has a simple process, low cost, and a calcination temperature of no more than 450°C, so that its surface has a microporous structure, a larger specific surface area, is more conducive to the mineralization of the material, improves the biological activity of the material, and does not produce α-iron oxide, and has better magnetocaloric properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect of the present invention, a neutral magnetic bioactive glass is provided, wherein the neutral magnetic bioactive glass is obtained by calcining a nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide, and ferrosoferric oxide at low temperature;
[0008] The preparation method of the nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide is as follows:
[0009] Sodium metasilicate pentahydrate is prepared into a transparent sodium silicate colloid;
[0010] Adding a calcium ion solution dropwise into the sodium silicate transparent colloid to perform a coprecipitation reaction to obtain a white colloid;
[0011] Adding magnesium oxide and ferroferric oxide to the white colloid, then dropping sulfuric acid solution until neutral and stirring, filtering and aging at 60-80° C. for 24-48 hours to obtain a nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide;
[0012] The low temperature calcination comprises:
[0013] The first stage: heating from 25-35℃ to 150-160℃ at a rate of 5-10℃ / min, keeping warm for 2-3h;
[0014] The second stage: then heat up to 400-450℃ at a rate of 8-10℃ / min and keep warm for 1.5-2.5h;
[0015] After the low-temperature calcination, the ferroferric oxide is oxidized to magnetic γ-iron oxide.
[0016] Furthermore, the chemical composition of the neutral magnetic bioactive glass is calculated in a molar ratio of silicon dioxide: calcium sulfate: magnesium oxide: gamma-iron oxide = 10: 1-3: 0.5: 0.15-1.5.
[0017] Furthermore, the particle size of the neutral magnetic bioactive glass is 0.1 μm to 20 μm.
[0018] A second aspect of the present invention provides a method for preparing a neutral magnetic bioactive glass, the method comprising:
[0019] Sodium metasilicate pentahydrate is prepared into a transparent sodium silicate colloid;
[0020] Adding a calcium ion solution dropwise into the sodium silicate transparent colloid to perform a coprecipitation reaction to obtain a white colloid;
[0021] Adding magnesium oxide and ferroferric oxide to the white colloid, then dropping sulfuric acid solution until neutral and stirring, filtering and aging at 60-80° C. for 24-48 hours to obtain a nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide;
[0022] The nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide is calcined at low temperature, and then washed and dried to obtain neutral magnetic bioactive glass.
[0023] Furthermore, the calcium ion solution is a saturated calcium nitrate solution or a saturated calcium chloride solution.
[0024] Furthermore, the preparation of sodium metasilicate pentahydrate into a sodium silicate transparent colloid comprises:
[0025] Add sodium metasilicate pentahydrate into pure water, then add concentrated sulfuric acid until all the solids disappear to form a transparent sodium silicate colloid.
[0026] Furthermore, the concentration of the concentrated sulfuric acid is 25% to 35%.
[0027] Furthermore, the molar ratio of the sodium metasilicate pentahydrate, the magnesium oxide, the ferrosoferric oxide and the calcium ion solution is 10:0.5:0.1-1.0:1-3.
[0028] Furthermore, the ferroferric oxide is oxidized to magnetic γ-iron oxide during the low-temperature calcination; the low-temperature calcination comprises:
[0029] The first stage: heating from 25-35℃ to 150-160℃ at a rate of 5-10℃ / min, keeping warm for 2-3h;
[0030] The second stage: then heat up to 400-450°C at a rate of 8-10°C / min and keep warm for 1.5-2.5h.
[0031] Furthermore, in the drying, the drying is carried out at 80 to 120° C. for 5 to 10 hours.
[0032] In the third aspect of the present invention, there is provided a use of the neutral magnetic bioactive glass in the preparation of bone implant materials.
[0033] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0034] 1. The neutral magnetic bioactive glass provided by the present invention has a microporous structure on its surface due to the special synthesis process and the low calcination temperature of the material, which has a larger specific surface area, is more conducive to the mineralization of the material, and improves the biological activity of the material. The neutral magnetic bioactive glass has excellent biological activity, biocompatibility and osteogenic ability, and also has excellent magnetocaloric effect, and can be used to treat bone tumors.
[0035] 2. The preparation method of a neutral magnetic bioactive glass provided by the present invention breaks the conventional thinking of the prior art, adopts sodium silicate transparent colloid to co-precipitate to produce nano calcium sulfate, adds ferroferric oxide and magnesium oxide at the same time, and adopts calcination at a temperature not higher than 450°C to obtain a nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide;
[0036] At the same time, the magnesium oxide contained in the core-shell structure is used for bone repair, and calcium sulfate can promote material mineralization and improve bone formation ability; the calcium sulfate component is stable and does not need to be converted into calcium oxide, the calcination temperature is greatly reduced, and the specific surface area is increased; the magnetic component is pure γ-iron oxide, and no α-iron oxide is generated. The material does not contain alkaline substances such as sodium oxide and calcium oxide, the material is neutral (alkaline implantation has a stimulating effect on the human body), and has better biocompatibility; the method has a short synthesis cycle, low cost, and is more conducive to industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 is a SEM image of the neutral magnetic bioactive glass of Example 2 of the present invention;
[0039] Figure 2 is an XRD graph of the neutral magnetic bioactive glass of Example 2 of the present invention;
[0040] Figure 3 The cytotoxicity results of the neutral magnetic bioactive glass of Example 2 of the present invention;
[0041] Figure 4 The pH value variation curves of the neutral magnetic bioactive glass of Example 2 of the present invention and the bioactive glass of Comparative Example 1;
[0042] Figure 5 This is an infrared thermal image of the magnetocaloric properties of the neutral magnetic bioactive glass of Example 2 of the present invention. DETAILED DESCRIPTION
[0043] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0044] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or obtained by existing methods.
[0046] The embodiment of the present invention provides a neutral magnetic bioactive glass, and the overall idea is as follows:
[0047] According to a typical embodiment of the present invention, a neutral magnetic bioactive glass is provided, wherein the neutral magnetic bioactive glass is obtained by calcining a nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide, and ferrosoferric oxide at low temperature;
[0048] The preparation method of the nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide is as follows:
[0049] Sodium metasilicate pentahydrate is prepared into a transparent sodium silicate colloid;
[0050] Adding a calcium ion solution dropwise into the sodium silicate transparent colloid to perform a coprecipitation reaction to obtain a white colloid;
[0051] Adding magnesium oxide and ferroferric oxide to the white colloid, then dropping sulfuric acid solution until neutral and stirring, filtering and aging at 60-80° C. for 24-48 hours to obtain a nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide;
[0052] The low temperature calcination comprises:
[0053] The first stage: heating from 25-35℃ to 150-160℃ at a rate of 5-10℃ / min, keeping warm for 2-3h;
[0054] The second stage: the temperature is then raised to 400-450°C at a rate of 8-10°C / min and kept at this temperature for 1.5-2.5 hours. After the low-temperature calcination, the ferroferric oxide is oxidized to magnetic γ-iron oxide.
[0055] In the above technical scheme, in the nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide, and ferroferric oxide, calcium sulfate, magnesium oxide, and ferroferric oxide are all located in the porous material. After low-temperature calcination, the ferroferric oxide is oxidized to magnetic γ-iron oxide. The present invention adopts a temperature of not more than 450°C for calcination to obtain a nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide, and ferroferric oxide; due to the special synthesis process and the low calcination temperature of the material, the surface thereof has a microporous structure, a larger specific surface area, and is more conducive to the mineralization of the material, thereby improving the biological activity of the material. The magnetic component is a pure γ-iron oxide, and no α-iron oxide is generated. The material does not contain alkaline substances such as sodium oxide and calcium oxide, and the material is neutral (alkaline implantation into the human body has a stimulating effect), and has more excellent biocompatibility; the method has a short synthesis cycle, low cost, and is more conducive to industrialization.
[0056] The reason for adopting the above-mentioned segmented low-temperature calcination is that under the condition of 150-160°C, the silica gel in the silicon-based porous material can further undergo condensation reaction while dehydrating the calcium sulfate dihydrate, slowly releasing water vapor, and providing conditions for constructing a porous structure; 400-450°C can completely dehydrate the silica gel to generate silicon dioxide, oxidize ferric oxide to γ-iron oxide, and avoid the conversion of γ-iron oxide to α-iron oxide.
[0057] In the above technical solution, the chemical composition of the neutral magnetic bioactive glass is calculated in a molar ratio of silicon dioxide: calcium sulfate: magnesium oxide: γ-iron oxide = 10: 1-3: 0.5: 0.15-1.5.
[0058] In the above technical solution, the particle size of the neutral magnetic bioactive glass is 0.1 μm to 20 μm, which can be controlled by adjusting the solid-liquid ratio and the calcium ion content.
[0059] According to a typical embodiment of the present invention, a method for preparing neutral magnetic bioactive glass is provided, the method comprising:
[0060] Step S1, preparing sodium metasilicate pentahydrate into a sodium silicate transparent colloid;
[0061] As an optional implementation, the step S1 includes:
[0062] Add sodium metasilicate pentahydrate into pure water, then add concentrated sulfuric acid until all the solids disappear to form sodium silicate transparent glue;
[0063] The concentration of the concentrated sulfuric acid is usually 25-35%; in other embodiments, the concentrated sulfuric acid may be replaced by hydrochloric acid;
[0064] Step S2, adding a calcium ion solution dropwise to the sodium silicate transparent colloid to perform a coprecipitation reaction to obtain a white colloid;
[0065] The calcium ion solution is a saturated calcium nitrate solution or a saturated calcium chloride solution.
[0066] Step S3, adding magnesium oxide and ferroferric oxide to the white colloid, then dropping sulfuric acid solution until neutral and stirring, filtering and aging at 60-80° C. for 24-48 hours to obtain a nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide;
[0067] Step S4, calcining the nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferrosoferric oxide at low temperature, and then washing and drying to obtain neutral magnetic bioactive glass.
[0068] In the drying, the drying is performed at 80 to 120° C. for 5 to 10 hours.
[0069] The molar ratio of the sodium metasilicate pentahydrate, the magnesium oxide, the ferroferric oxide and the calcium ion solution is 10:0.5:0.1-1.0:1-3.
[0070] The present invention also provides the use of the neutral magnetic bioactive glass in the preparation of bone implant materials. Due to its excellent performance, the obtained neutral magnetic bioactive glass can be used in combination with a variety of materials to obtain more uses. For example, it can be used in combination with materials such as calcium sulfate, calcium phosphate, PMMA, cellulose, sodium hyaluronate, etc. to enable it to have injection capabilities for minimally invasive treatment; it can be used in combination with materials such as polylactic acid, gelatin, and silk fibroin to perform 3D printing, so that it has a more refined structure and realizes personalized customization.
[0071] The neutral magnetic bioactive glass of the present application will be described in detail below in combination with examples and experimental data.
[0072] Example 1: A neutral magnetic bioactive glass and its preparation method
[0073] The embodiment of the present invention provides a neutral magnetic bioactive glass, and the preparation method is as follows:
[0074] 1. Add 21.2g of sodium metasilicate pentahydrate to 50mL of purified water, and add 30% concentrated sulfuric acid dropwise until all the solid disappears and a transparent colloid is formed;
[0075] 2. Add 10 mL of 1M calcium chloride solution to the transparent colloid of sodium metasilicate pentahydrate, stir for 1 hour for coprecipitation reaction to obtain a white colloid, then add 0.2 g of magnesium oxide and 2.3 g of ferrosoferric oxide, and finally add sulfuric acid solution dropwise until neutral, continue stirring for 2 hours, filter, age at 80°C for 24 hours, and then calcine using the following procedure:
[0076] The first stage: heating from 30℃ to 160℃ at a rate of 10℃ / min, and keeping warm for 3h;
[0077] The second stage: then raise the temperature to 450°C at 10°C / min and keep it for 2h.
[0078] 3. After calcination, the glass was cleaned and then dried at 105°C for 6 hours to obtain neutral magnetic bioactive glass with a total heavy metal content of <50 ppm.
[0079] Example 2: A neutral magnetic bioactive glass and its preparation method
[0080] The embodiment of the present invention provides a neutral magnetic bioactive glass, and the preparation method is as follows:
[0081] 1. Add 21.2g of sodium metasilicate pentahydrate to 50mL of purified water, and add 30% concentrated sulfuric acid dropwise until all the solid disappears and a transparent colloid is formed;
[0082] 2. Add 10 mL of 2M calcium chloride solution to the transparent colloid of sodium metasilicate pentahydrate, stir for 1 hour for coprecipitation reaction to obtain a white colloid, then add 0.2 g of magnesium oxide and 2.0 g of ferrosoferric oxide, and finally add sulfuric acid solution dropwise until neutral, continue stirring for 3 hours, filter, age at 80°C for 48 hours, and then calcine using the following procedure:
[0083] The first stage: heating from 30℃ to 160℃ at a rate of 5℃ / min, and keeping warm for 2h;
[0084] The second stage: then raise the temperature to 450°C at 10°C / min and keep it for 2h.
[0085] 3. After calcination, the glass was cleaned and then dried at 110°C for 8 hours to obtain neutral magnetic bioactive glass with a total heavy metal content of <50 ppm.
[0086] Example 3: A neutral magnetic bioactive glass and its preparation method
[0087] The embodiment of the present invention provides a neutral magnetic bioactive glass, and the preparation method is as follows:
[0088] 1. Add 21.2g of sodium metasilicate pentahydrate to 50mL of purified water, and add 30% concentrated sulfuric acid dropwise until all the solid disappears and a transparent colloid is formed;
[0089] 2. Add 10 mL of 3M calcium chloride solution to the transparent colloid of sodium metasilicate pentahydrate, stir for 1 hour for coprecipitation reaction to obtain a white colloid, then add 0.2 g of magnesium oxide and 1.0 g of ferrosoferric oxide, and finally add sulfuric acid solution dropwise until neutral, continue stirring for 2 hours, filter, age at 60°C for 48 hours, and then calcine using the following procedure:
[0090] The first stage: heating from 30℃ to 150℃ at a rate of 8℃ / min, and keeping warm for 3h;
[0091] The second stage: then raise the temperature to 420℃ at 8℃ / min and keep it for 2.5h.
[0092] 3. After calcination, the glass was cleaned and then dried at 90°C for 10 hours to obtain neutral magnetic bioactive glass with a total heavy metal content of <50 ppm.
[0093] Example 4: A neutral magnetic bioactive glass and its preparation method
[0094] The embodiment of the present invention provides a neutral magnetic bioactive glass, and the preparation method is as follows:
[0095] 1. Add 21.2g of sodium metasilicate pentahydrate to 50mL of purified water, and add 30% concentrated sulfuric acid dropwise until all the solid disappears and a transparent colloid is formed;
[0096] 2. Add 10 mL of 2M calcium chloride solution to the transparent colloid of sodium metasilicate pentahydrate, stir for 1 hour for coprecipitation reaction to obtain a white colloid, then add 0.2 g of magnesium oxide and 1.5 g of ferrosoferric oxide, and finally add sulfuric acid solution dropwise until neutral, continue stirring for 2 hours, filter, age at 70°C for 40 hours, and then calcine using the following procedure:
[0097] The first stage: heating from 30℃ to 160℃ at a rate of 10℃ / min, and keeping warm for 2h;
[0098] The second stage: then raise the temperature to 450°C at 10°C / min and keep it for 2h.
[0099] 3. After calcination, the glass was cleaned and then dried at 105°C for 8 hours to obtain neutral magnetic bioactive glass with a total heavy metal content of <50 ppm.
[0100] Experimental Example 1: Performance Measurement
[0101] The properties of the neutral magnetic bioactive glass prepared in Example 2 of the present invention were tested;
[0102] 1. SEM image
[0103] The SEM image of the neutral magnetic bioactive glass described in Example 2 of the present invention is as follows: Figure 1 As shown, it can be seen that the surface of the neutral magnetic bioactive glass is a porous structure, and nano-sized crystal particles can be seen on the surface, indicating that the material has a high specific surface area, which can help the degradation of the material and the surface ion exchange, thereby facilitating the deposition of hydroxyapatite on the surface, thus having better biological activity.
[0104] 2. XRD pattern
[0105] The XRD curve of the neutral magnetic bioactive glass of Example 2 of the present invention is as follows: Figure 2 As shown, only the characteristic peak of γ-iron oxide is visible, indicating that no α-iron oxide is produced, only γ-iron oxide with magnetic properties, which makes the material have better magnetic properties.
[0106] 3. Cytotoxicity assay
[0107] The cytotoxicity test method was carried out according to GB / T 16886.5;
[0108] The results are as follows Figure 3 It can be seen that the material obtained by MBG / CS (Example 2) is non-toxic and shows good biocompatibility.
[0109] 4. pH value of the extract
[0110] The pH value variation curve of the neutral magnetic bioactive glass extract of Example 2 of the present invention is as follows: Figure 4 As shown, compared with MBG (Comparative Example 1), its pH value is maintained below 9, while the pH value of MBG is close to 11, which is obviously alkaline.
[0111] 5. Infrared thermal image of magnetic thermal performance
[0112] The infrared thermal image of the magnetothermal performance of the neutral magnetic bioactive glass of Example 2 of the present invention is as follows: Figure 5 As shown, it can be seen that under the action of the alternating magnetic field, the temperature of the material increases rapidly, reaching 106°C after 60 seconds and rising to 121°C after 120 seconds, reflecting an obvious magnetocaloric effect.
[0113] In summary, compared with traditional bioactive glass, the neutral magnetic bioactive glass of the embodiment of the present invention has a pH value maintained at neutral or weak alkaline due to its special composition, which makes it more biocompatible and less likely to cause tissue redness, swelling and exudation; due to its special surface structure and nanocrystalline morphology, it is easier to deposit apatite on the surface after implantation in the body, so that it can combine with surrounding tissues faster, thereby improving its biocompatibility and bone formation ability. At the same time, it also has magnetism, making it potentially useful for treating bone tumors. It can also be used in combination with a variety of materials, making its application range wider.
[0114] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0115] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0116] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A neutral magnetic bioactive glass, characterized in that: The neutral magnetic bioactive glass is obtained by calcining nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide at low temperature; The preparation method of the nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide is as follows: Sodium metasilicate pentahydrate is prepared into a transparent sodium silicate colloid; Adding a calcium ion solution dropwise into the sodium silicate transparent colloid to perform a coprecipitation reaction to obtain a white colloid; Adding magnesium oxide and ferroferric oxide to the white colloid, then dropping sulfuric acid solution until neutral and stirring, filtering and aging at 60-80° C. for 24-48 hours to obtain a nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide; The low temperature calcination comprises: The first stage: heating from 25-35℃ to 150-160℃ at a rate of 5-10℃ / min, keeping warm for 2-3h; The second stage: then heat up to 400-450℃ at a rate of 8-10℃ / min and keep warm for 1.5-2.5h; After the low-temperature calcination, the ferroferric oxide is oxidized to magnetic γ-iron oxide.
2. The neutral magnetic bioactive glass according to claim 1, characterized in that: The chemical composition of the neutral magnetic bioactive glass is calculated in molar ratio as follows: silicon dioxide: calcium sulfate: magnesium oxide: gamma-iron oxide = 10: 1-3: 0.5: 0.15-1.
5.
3. A method for preparing the neutral magnetic bioactive glass according to any one of claims 1 to 2, characterized in that: The method comprises: Sodium metasilicate pentahydrate is prepared into a transparent sodium silicate colloid; Adding a calcium ion solution dropwise into the sodium silicate transparent colloid to perform a coprecipitation reaction to obtain a white colloid; Adding magnesium oxide and ferroferric oxide to the white colloid, then dropping sulfuric acid solution until neutral and stirring, filtering and aging at 60-80° C. for 24-48 hours to obtain a nanoparticle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide; The nano-particle silicon-based porous material loaded with calcium sulfate, magnesium oxide and ferroferric oxide is calcined at low temperature, and then washed and dried to obtain neutral magnetic bioactive glass.
4. The method for preparing a neutral magnetic bioactive glass according to claim 3, characterized in that: The calcium ion solution is a saturated calcium nitrate solution or a saturated calcium chloride solution.
5. The method for preparing a neutral magnetic bioactive glass according to claim 3, characterized in that: The method of preparing sodium metasilicate pentahydrate into a sodium silicate transparent colloid comprises: Add sodium metasilicate pentahydrate into pure water, then add concentrated sulfuric acid until all the solids disappear to form a transparent sodium silicate colloid.
6. The method for preparing a neutral magnetic bioactive glass according to claim 5, characterized in that: The concentration of the concentrated sulfuric acid is 25% to 35%.
7. The method for preparing a neutral magnetic bioactive glass according to claim 3, characterized in that: The molar ratio of the sodium metasilicate pentahydrate, the magnesium oxide, the ferroferric oxide and the calcium ion solution is 10:0.5:0.1-1.0:1-3.
8. The method for preparing a neutral magnetic bioactive glass according to claim 3, characterized in that: The low-temperature calcination oxidizes the ferroferric oxide into magnetic γ-iron oxide; the low-temperature calcination comprises: The first stage: heating from 25-35℃ to 150-160℃ at a rate of 5-10℃ / min, keeping warm for 2-3h; The second stage: then heat up to 400-450°C at a rate of 8-10°C / min and keep warm for 1.5-2.5h.
9. The method for preparing a neutral magnetic bioactive glass according to claim 3, characterized in that: In the drying, the drying is performed at 80 to 120° C. for 5 to 10 hours.
10. Use of the neutral magnetic bioactive glass according to any one of claims 1 to 2 in the preparation of bone implant materials.
Citation Information
Patent Citations
A magnetic bioactive glass, its preparation method and application
CN113429127B
Bone substitute containing porous bio-glass and calcium sulphate
CN102170922A
Magnetic bioactive glass as well as preparation method and application thereof
CN113429127A